Strategies for cadmium detoxification in the white shrimp Palaemon argentinus from clean and polluted field locations - Chiodi Boudet, Leila (2019)
In this study, we investigated the metal handling capacity of non-tolerant and tolerant populations of Palaemon argentinus to cadmium (Cd), through evaluating of the main mechanisms of metal detoxification, metallothioneins (MT), and metal-rich granules (MRG), to prove that the presence of MRG in the second population is responsible for that condition. The tolerant population were exposed to 3.06 and 12.26 mg Cd$L 1, while the non-tolerant shrimp were exposed to 3.06 mg Cd$L 1. Each experiment involved the exposure during 3, 7, 10, and 15 days and, the depuration during 7, 14, 21, and 28 days, for which shrimp were transferred to clean water. The range values of MT concentrations for non-tolerant shrimp were: 12.24e23.91 mg g (w.w), while for tolerant shrimp were: 8.75e16.85 mg g (w.w); MRG levels were: 0.12e0.57 mg g (w.w) and 0.3e2.1 mg g (w.w), respectively. The results showed different strategies for Cd detoxification: the induction of MT was the main pathway in the non-tolerant population, while the formation of Cd-MRG was the main mechanism for tolerant shrimp. These differences could be related to environmental history and the health status of each population.